Active Knowledge Sharing in Online Group Work - Bo Chang (Adult Education Research Conference, 2016)
The purpose of this paper is to explore how to support active knowledge sharing and creation in an online group work which both encourages collaboration and motivates individual effort.
Keywords: Knowledge sharing; online group work; course design